Insights into the Mechanism of Oxygen-mediated Growth Arrest of Bacteroides fragilis. - Meehan, Brian. (2017)
Abstract: The goal of this work was to define the factors that inhibit growth of Bacteroides fragilisat oxygen levels > 0.05%. One important aspect of this growth arrest is the accumulation of endogenously-generated reactive oxygen species (ROS) like hydrogen peroxide (H2O2). We show here that H2O2 scavenging rates were reduced to 20% of the wild-type in a strain missing alkylhydroperoxide reductase (ahpC), catalase, and thioredoxin-dependent peroxidase (tpx). This strain was hypersensitive to room air and was found to generate ROS at a rate of ~35nM/min/OD600=0.1 under these conditions. However, deletion of fumarate reductase gave rise to a strain that accumulated ~19nM H2O2/min//OD600=0.1, indicating that this enzyme accounts for ~47% of the ROS generated by aerated B. fragilis. Deleting frdC increased the aerotolerance of a Δsod strain by ~100-fold during 9 hours of exposure to room air. Spontaneous mutants of B. fragilis capable of growth under 1% oxygen arise at a frequency of ~10-6. These strains carried mutations in an orf designated oxe. Deletion of oxe established the O2-enabled phenotype, and this mutant could be re-sensitized to oxygen by providing a wild-type copy of oxe in trans. Microaerobic growth of the Δoxe strain was characterized by several amino acid auxotrophies. Though Oxe is not a major source of ROS under room air, a Δoxe strain was found to scavenge micromolar amounts of H2O2 at a rate approximately triple that of the wild-type. Fecal strains of B. fragilis did not grow under ~1% oxygen. Ten clinical strains plated microaerobically with efficiencies greater than 10%, 14 plated with frequencies similar to the fecal strains, and 7 had an intermediate phenotype. The oxe locus was sequenced for 7 clinical strains that plated with high efficiencies microaerobically and four were found to encode a wild-type Oxe, while 3 were predicted to contain amino acid substitutions in Oxe. Oxe may contribute to the utilization of amino sugars by B. fragilis, as a Δoxe strain bearing a mutant allele of nagB could not grow on N-acetylglucosamine or glucosamine. However, the role of Oxe in the anaerobic physiology of this organism is still under investigation.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Michael Malamy.; Committee: Andrew Camilli, Andrew Wright, and Ralph Isberg.; Keyword: Microbiology.